The performance of concentrated solar power (CSP) systems : analysis, measurement and assessment - Heller, Peter (Aerospace engineer) (Woodhead Publishing in energy., 2017)
This book offers an overview of the information on the state-of-the-art of analysis, measurement, and assessment of the performance of concentrated solar power (CSP) components and systems in a comprehensive, compact, and complete manner. Following an introductory chapter to CSP systems and the fundamental principles of performance assessment, individual chapters explore the component performance of mirrors and receivers. Further expert-written chapters look at system performance assessment, durability testing, and solar resource forecasting for CSP systems. A final chapter gives an outlook on the actual methods and instruments for performance and durability assessment that are under development.